2012
DOI: 10.1177/1040638712452730
|View full text |Cite
|
Sign up to set email alerts
|

Application of quantitative real-time polymerase chain reaction for the diagnosis of toxoplasmosis and enzootic abortion of ewes

Abstract: Toxoplasma gondii and Chlamydophila abortus are the 2 most common infectious causes of ovine abortion worldwide. These obligate intracellular pathogens are associated with severe placentitis leading to abortion or stillbirth in pregnant ewes, and resulting in significant economic losses. The objectives of the current study were the development, validation, and application of a duplex real-time polymerase chain reaction (PCR) assay capable of quantifying the burden of infection by T. gondii and C. abortus in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
1
24
2
Order By: Relevance
“…The study had similar findings to the present study in that C. abortus and T. gondii were commonly identified with other pathogens in the same abortion case. 12 Campylobacter spp. was only identified in sheep, and several submissions were from the same farm.…”
Section: Discussionmentioning
confidence: 99%
“…The study had similar findings to the present study in that C. abortus and T. gondii were commonly identified with other pathogens in the same abortion case. 12 Campylobacter spp. was only identified in sheep, and several submissions were from the same farm.…”
Section: Discussionmentioning
confidence: 99%
“…Placenta and foetal brain and liver samples that had tested positive by nested-PCR were adjusted to 20 ng DNA/μL and the parasite load was quantified using real-time PCR. Primer pairs from the N. caninum Nc-5 sequence [ 25 ] were used for parasite quantification, and primers from the β-actin gene [ 26 ] were used for the quantification of host DNA. Amplification reactions were performed as described by Collantes-Fernández et al [ 25 ], in a final volume of 20 μL using Power SYBR® Green PCR Master Mix (Applied Biosystems, Foster City¸ CA, USA), 20 pmol of each primer and 100 ng of DNA in a ABI 7300 Real Time PCR System (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental infection of sheep with Neospora caninum has shown that there is a close relation between parasite burden and the severity of lesions identified in placenta or foetus, and how these parameters could affect the course of clinical disease [ 8 ]. The close relationship between the presence of T. gondii and the development of histological lesions has been shown through quantitative real time-PCR (qPCR), in sheep experimentally infected at mid gestation [ 9 ]. Whether there are differences in the quantity of parasite and the presence of lesions at different terms of gestation in ovine toxoplasmosis has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%